2018
DOI: 10.21873/anticanres.12343
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypofractionated Radiation Therapy in Prostate Carcinoma: A Systematic Review

Abstract: Acute toxicity does not seem to be increased in patients receiving postoperative HFRT, but the results of late-GU toxicity are conflicting. Further prospective studies are needed before including postoperative HFRT in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Consistent with these findings, at the time of the final analysis, the impact of our schedule in terms of biochemical control reflects in a 3-year bRFS of 73% rate in agreement with literature data ranging from 72.9% to 85.5% at 2–3 years 20 , confirming the efficacy of our treatment schedule.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with these findings, at the time of the final analysis, the impact of our schedule in terms of biochemical control reflects in a 3-year bRFS of 73% rate in agreement with literature data ranging from 72.9% to 85.5% at 2–3 years 20 , confirming the efficacy of our treatment schedule.…”
Section: Discussionsupporting
confidence: 91%
“…Our clinical experience with postprostatectomy moderate hypofractionation using HT confirmed that, with this delivery technique, toxicities are quite low and similar to those observed in other hypofractionation studies in this setting. 20 …”
Section: Discussionmentioning
confidence: 99%
“…There was larger heterogeneity regarding late effects, which may be attributed to difference in follow-up and treatment technique. Another systematic review by Siepe et al [38] included 17 studies, of which seven were retrospective. Each of three-dimensional conformal radiotherapy and volumetric modulated arc therapy was used in two series, while 12 trials treated men with IMRT, of which five employed a simultaneous integrated boost.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The authors attributed the high late toxicity to outdated radiotherapy techniques in some of the included trials. They concluded that the use of androgen deprivation therapy and inclusion of regional lymph nodes did not worsen toxicity [38] .…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Although hypofractionation is standard of care in the primary PCa setting, data on hypofractionated sEBRT are scarce. A recently published systematic review supports the tolerance of hypofractionated sEBRT, but stresses the importance of conducting RCTs comparing hypofractionated with standard fractionated sEBRT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%